The Identification of Inflation Rate Determinants in the USA Using the Stochastic Search Variable Selection - Mihaela Simionescu (CES Working Papers, 2016)
Inflation rate determinants for the USA have been analyzed in this study starting with 2008, when the American economy was already in crisis. This research brings, as a novelty, the use of Bayesian Econometrics methods to identify the monthly inflation rate in the USA. The Stochastic Search Variable Selection (SSVS) has been applied for a subjective probability acceptance of 0.3. The results are validated also by economic theory. The monthly inflation rate was influenced during 2008-2015 by: the unemployment rate, the exchange rate, crude oil prices, the trade weighted U.S. Dollar Index and the M2 Money Stock. The study might be continued by considering other potential determinants of the inflation rate.
Keywords: C52; E31; 330; inflation rate; stochastic search; crisis; prices